1982
DOI: 10.1159/000215038
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur zellulären Immunität bei Mammakarzinompatientinnen

Abstract: Bei 84 Mammakarzinompatientinnen wurde präoperativ die zelluläre Immunität untersucht. 47 Patientinnen waren frei von regionären und Fernmetastasen, 37 Patientinnen hatten bereits axilläre Lymphkno-ten- aber noch keine Fernmetastasen. Als Kontrollkollektiv dienten 32 klinisch gesunde Frauen. In bezug auf die Leukozytenzahl und den prozentualen T-Zell-Anteil an der Gesamtlymphozytenpopulation ergaben sich zwischen gesunden Frauen und den Mammakarzinompatientinnen keine Unterschiede. Die Karzinompatientinnen wie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1986
1986

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Indirect evidence also comes from the study of Spielman et al [19]. They showed that in axillary lymph node positive patients, in whom the incidence of micrometastasis is higher, the lymphocyte count was higher than axillary lymph node negative cases.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence also comes from the study of Spielman et al [19]. They showed that in axillary lymph node positive patients, in whom the incidence of micrometastasis is higher, the lymphocyte count was higher than axillary lymph node negative cases.…”
Section: Discussionmentioning
confidence: 99%